Genetic association and functional implications of AhR gene polymorphism on preeclampsia - Jiang, Hong; Meng, Haiyun; Ma, Yantuanjin; Qian, Yuan; Chen, Xuerong; Luo, Lan; Yang, Yuling (Frontiers in Cardiovascular Medicine, 2025)
BackgroundPreeclampsia is one of the main causes of increased maternal and infant mortality and morbidity during pregnancy. The aryl hydrocarbon receptor (AhR) is a ligand-activated transcription factor ubiquitously found in mammals that can directly or indirectly regulate various physiological processes when activated.MethodsIn this case-control study, 74 patients with preeclampsia and 120 healthy pregnant controls were recruited. SNaPshot technology was used to detect genetic polymorphisms in four TagSNPs of the AhR gene. In addition, quantitative real-time PCR and western blotting were used to detect the expression of AhR in placental tissues from 21 patients with preeclampsia and 20 healthy controls. Subsequently, siRNA and drug treatment were used in vitro studies to knock down and inhibit AhR expression in human umbilical vein endothelial cells (HUVECs).ResultsThe allele frequency of rs713150G in the preeclampsia group was lower than that in the control group (OR = 0.467, 95% CI = 0.286-0.763; P = 0.002). Detection of AhR expression levels in placental tissue revealed that individuals who did not carry the rs713150G allele had lower expression of AhR in placental tissue than did those who carried the rs713150G allele, and lower AhR expression and nuclear translocation were positively correlated with the occurrence of preeclampsia. In vitro studies revealed that low expression of AhR in HUVECs suppressed the AhR signalling pathway, inhibited the expression of vascular endothelial growth factor A (VEGF-A), and inhibited the tube formation of HUVECs. And inhibition of AhR activity had a similar effect.ConclusionThe AhR gene polymorphism is associated with susceptibility of preeclampsia in the Chinese population and share in its pathogenesis as noncarriage of rs713150G leads to low expression of AhR in placental tissue that subsequently might participate in the development of preeclampsia by inhibiting placental angiogenesis.